2016
DOI: 10.4028/www.scientific.net/amr.1139.55
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Titanium Cenosphere Composite Developed by Powder Metallurgy Route

Abstract: The present study concerns detailed microstructural investigation and property evaluation of titanium-cenosphere composite developed by powder metallurgy route. The main process variables for the development of titanium-cenosphere composite were cenosphere particle size, sintering time, and sintering temperature. Followed by sintering, a detailed characterization of the sintered parts in terms of density, microstructure, composition and phase has been carried out. The compressive strength of the sintered compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…A detailed study of the effect of sintering parameters and cenosphere particle size on the percentage of porosity present and density achieved in titanium-cenosphere composites showed that a significant decrease in density is achieved in sintered pellets (1.9 to 2.5 gm/cc) as compared to as received titanium (4.5 gm/cc) and was found to vary with particle size of cenosphere, sintering time and temperature [14]. It was further concluded that optimization of process parameters are essential to avoid damage of cenosphere particles and development of defect free and continuous interface between ceosphere and titanium in the composite [14]. Decrease in density in the composite is attributed to the presence of cenosphere and porosities in the matrix due to development of the material by conventional powder processing route.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed study of the effect of sintering parameters and cenosphere particle size on the percentage of porosity present and density achieved in titanium-cenosphere composites showed that a significant decrease in density is achieved in sintered pellets (1.9 to 2.5 gm/cc) as compared to as received titanium (4.5 gm/cc) and was found to vary with particle size of cenosphere, sintering time and temperature [14]. It was further concluded that optimization of process parameters are essential to avoid damage of cenosphere particles and development of defect free and continuous interface between ceosphere and titanium in the composite [14]. Decrease in density in the composite is attributed to the presence of cenosphere and porosities in the matrix due to development of the material by conventional powder processing route.…”
Section: Resultsmentioning
confidence: 99%
“…Increase in sintering temperature and sintering time was found to increase density of the composite. However, among all variables, the particle size of cenosphere directly influences the density of the composites [14].…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical properties in terms of compressive stress (yield stress and Young's modulus) of these samples have already been reported in a different publication by the same authors. [25] From the literature, it has been found that the yield strength and Young's modulus value of these types of Ticenosphere composite materials fall between 21-58 MPa and 25-42 GPa, respectively. [23] Similar values of mechanical properties were obtained in studies conducted by a group where the samples also showed promising in-vivo behavior in terms of new bone growth when implanted in a white rabbit in New Zealand and observed for one and three months, respectively.…”
Section: Chemistryselectmentioning
confidence: 99%
“…Among the few studies that explored the cenosphere addition in Ti foam, the influence of cenosphere particle size and the process parameters on the wear behavior of Ti foam [25,28] is worth mentioning. The corrosion rate of Ti foam was found to be at a significantly lower rate than that of solid Ti.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2] There are several kinds of hard ceramic nanoparticles, e.g., SiC, B 4 C, TiC, TiB 2 , Al 2 O 3 and soft reinforcements, e.g., MoS 2 or Gr, used as the reinforcements in aluminum alloys to improve the mechanical characteristics. [3][4][5][6][7] However, many researchers suggested that titanium carbide is the most effective ceramic particle as that it has a good range of wettability and a high specific strength within an aluminum alloy. [8][9] The machinability can be improved by adding graphite to a metal-matrix composite (MMC).…”
Section: Introductionmentioning
confidence: 99%